Pastoral Care during Economic Crisis - Rosell, Ruth Lofgren (Review and expositor, 2010)
Although the economic recession is lessening, still many in our churches and communities need pastoral care. This article assists pastors and congregations in exploring how to respond. Of primary importance is for pastors to respond with a pastoral presence that is representative of both God and the faith community and that provides support and strength to those experiencing high levels of anxiety. It is also noted how unexamined cultural bias against those who are poor can greatly undermine efforts to be present pastorally during financial need. Attention is given to addressing the crises people are facing, care for the grief involved, support for adjustment to job loss, support during the job search, help in stabilizing financial situations, response to the presence of depression, and encouragement to reevaluation life's values and goals.